2017
DOI: 10.1002/bies.201600246
|View full text |Cite
|
Sign up to set email alerts
|

Hox functional diversity: Novel insights from flexible motif folding and plastic protein interaction

Abstract: How the formidable diversity of forms emerges from developmental and evolutionary processes is one of the most fascinating questions in biology. The homeodomain-containing Hox proteins were recognized early on as major actors in diversifying animal body plans. The molecular mechanisms underlying how this transcription factor family controls a large array of context- and cell-specific biological functions is, however, still poorly understood. Clues to functional diversity have emerged from studies exploring how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…During development, HOX proteins can bind similar AT-rich DNA sequences in vitro (for reviews, see McGinnis and Krumlauf 1992;Gehring et al 1994;Lemons and McGinnis 2006). HOX proteins can heterodimerize with PBX/ Exd proteins (see Saadaoui et al 2011;Ladam and Sagerström 2014;Merabet and Mann 2016;Ortiz-Lombardia et al 2017) and can also pair with other classes of TFs for function; for example T-box factors, as recently described in limb development (Jain et al 2018). Through the years, heterodimerization with PBX/Exd has been proposed as a mechanism through which HOX proteins acquire DNA-binding selectivity and specificity.…”
Section: Partnerships Of Pbc Tfsmentioning
confidence: 99%
“…During development, HOX proteins can bind similar AT-rich DNA sequences in vitro (for reviews, see McGinnis and Krumlauf 1992;Gehring et al 1994;Lemons and McGinnis 2006). HOX proteins can heterodimerize with PBX/ Exd proteins (see Saadaoui et al 2011;Ladam and Sagerström 2014;Merabet and Mann 2016;Ortiz-Lombardia et al 2017) and can also pair with other classes of TFs for function; for example T-box factors, as recently described in limb development (Jain et al 2018). Through the years, heterodimerization with PBX/Exd has been proposed as a mechanism through which HOX proteins acquire DNA-binding selectivity and specificity.…”
Section: Partnerships Of Pbc Tfsmentioning
confidence: 99%
“…The homeobox genes encode a large superclass of TFs ( Garcia-Fernandez 2005 ; Hoegg and Meyer 2005 ; Pascual-Anaya et al 2012 ; Holland 2015 ; Ferrier 2016 ). They are characterized by encoding a homeodomain, which is usually 60 amino acids in length and folds to form a structure with three α-helices and an N-terminal domain ( Ortiz-Lombardia et al 2017 ). The third α-helix and N-terminal domain confer the specificity to the binding of the homeodomain to the major and minor groove of the DNA double helix, respectively ( Hanes and Brent 1991 ; Chu et al 2012 ; Ortiz-Lombardia et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…They are characterized by encoding a homeodomain, which is usually 60 amino acids in length and folds to form a structure with three α-helices and an N-terminal domain ( Ortiz-Lombardia et al 2017 ). The third α-helix and N-terminal domain confer the specificity to the binding of the homeodomain to the major and minor groove of the DNA double helix, respectively ( Hanes and Brent 1991 ; Chu et al 2012 ; Ortiz-Lombardia et al 2017 ). This conservation of sequence facilitates the characterization of many homeobox genes based solely on their homeodomain sequence ( Holland et al 2007 ), although there are also a variety of other DNA binding domains found in metazoan homeobox genes, which provide additional identification characteristics and biological functions ( Burglin and Affolter 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Examples include: posterior Hox factors have greater affinity for adjacent Hth/Meis sites than anterior Hox factors [44,45], and Hox interactions with Exd/Pbx proteins via the Hox hexapeptide motif (YPWM) can uncover latent DNA binding specificity that better discriminates between Hox factors [19]. More recently, subsets of Hox factors have been shown to mediate additional interactions with Pbx/Exd proteins via specific PBC-interaction motifs (SPIMs) [14,15]. While SPIM interactions between Hox and PBC proteins are thought to be weaker and more dynamic than those mediated by the classic YPWM motif, it is possible they further aid in the ability of Hox factors to bind distinct DNA sequences.…”
Section: Discussionmentioning
confidence: 99%
“…A partial explanation for this phenomenon is that Hox factors form transcription factor complexes with additional proteins. The Extradenticle (Exd, Drosophila)/Pbx (vertebrate) and Homothorax (Hth, Drosophila)/Meis (vertebrate) families of transcription factors represent the best characterized Hox co-factor proteins [11][12][13][14][15]. Exd/Pbx and Hth/Meis proteins are widely expressed during development and bind DNA in a cooperative manner with Hox factors as well as with each other.…”
Section: Introductionmentioning
confidence: 99%